Pengaruh Beban Kerja dan Modernisasi Sistem Administrasi Perpajakan Terhadap Kinerja Karyawan di Kantor Pemerintah Xyz - Dina Permatasari; Ignatius Ario Sumbogo (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study aims to determine whether there is an influence between workload and the modernization of the tax administration system on the performance employees in the XYZ Government Office. This study uses a quantitative approach through distributing questionnaires to 100 XYZ Government Office employees. Hypothesis test results (t test) show that workload variables have a significant effect on employee performance variables. This is indicated by the value of t arithmetic of 3.375> t table 1.984 which is greater than t table. Likewise, the modernization of the tax administration system variable has a significant effect on employee performance variables with t count of 4.855> t table 1.984 which is greater than t table. The conclusion of this study is that the workload and modernization of the tax administration system have a significant effect on employee performance.